2022
DOI: 10.1016/j.yebeh.2021.108483
|View full text |Cite
|
Sign up to set email alerts
|

A post-approval observational study to evaluate the safety and tolerability of perampanel as an add-on therapy in adolescent, adult, and elderly patients with epilepsy

Abstract: Objective: Perampanel is a once-daily oral anti-seizure medication for focal-onset seizures, with or without focal to bilateral tonic-clonic seizures (FBTCS), and generalized tonic-clonic seizures. Study 402 (NCT02033902) collected safety information on clinically important treatment-emergent adverse events (TEAEs) from real-world clinical practice in patients aged !12 years with refractory epilepsy who were receiving perampanel as an add-on therapy. Methods: Study 402 was a multicenter, observational, 52-week… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 39 publications
2
14
1
Order By: Relevance
“…The main adverse reactions were: irritability, drowsiness, dizziness, nausea, vomiting and abnormal liver function. In a study of 493 epilepsy patients (including adolescents, adults, and the elderly), 28.2% of 243 patients who added perampanel had adverse reactions, mainly dizziness, irritability, balance disorders and weight gain ( 21 ). All adverse reactions were within the controllable range, and there was no situation that seriously affected the patient's vital signs or caused the recurrence and aggravation of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…The main adverse reactions were: irritability, drowsiness, dizziness, nausea, vomiting and abnormal liver function. In a study of 493 epilepsy patients (including adolescents, adults, and the elderly), 28.2% of 243 patients who added perampanel had adverse reactions, mainly dizziness, irritability, balance disorders and weight gain ( 21 ). All adverse reactions were within the controllable range, and there was no situation that seriously affected the patient's vital signs or caused the recurrence and aggravation of epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, as a real-world observational study, our study has the advantage of being able to obtain data from large heterogeneous populations of patients outside RCTs. 40 Findings from real-world observational studies such as ours mirror routine clinical practice more closely and could supplement findings from RCTs.…”
Section: Limitations and Strengthmentioning
confidence: 53%
“…Finally, as our follow‐up period was 1 year, longer follow‐ups might be needed to better assess treatment efficacy in those patients with low baseline frequency. On the other hand, as a real‐world observational study, our study has the advantage of being able to obtain data from large heterogeneous populations of patients outside RCTs 40 . Findings from real‐world observational studies such as ours mirror routine clinical practice more closely and could supplement findings from RCTs.…”
Section: Limitations and Strengthmentioning
confidence: 79%
“…In a recent meta-analysis, perampanel hydrate did not show the risk of suicidal ideation and suicidal attempt in patients without a history of suicidality; and suicidal ideation (including suicide attempt) was reported in only 3 of 1119 (0.27%) patients treated with perampanel hydrate ( 5 ). Conversely, suicidal ideation, intentional drug overdose, and suicide attempt were reported in 10 of 482 (2.1%) patients treated with perampanel hydrate, who had no medical history of suicidal behavior in an observational 52-week cohort study ( 21 ); although a history of suicidal behavior could not be determined, our results suggest that patients with epilepsy should be monitored for signs of suicidal behavior during treatment with perampanel hydrate. The neurobiological mechanism of suicidality is still unknown.…”
Section: Discussionmentioning
confidence: 65%
“…Antagonism of AMPA receptors by perampanel hydrate might be involved in suicidal behaviors, as indicated by the alteration of AMPA receptor function in patients who completed suicide. In addition, it has been reported that individuals taking perampanel hydrate have a high frequency of aggression, and that aggression is strongly correlated with suicidality risk ( 21 , 24 ). Aggression is associated with increased glutamate levels in the amygdala, hypothalamus, and periaqueductal gray matter, and with stimulation of glutamate receptors ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%